The DUF582 Proteins of Chlamydia trachomatis Bind to Components of the ESCRT Machinery, Which Is Dispensable for Bacterial Growth In vitro - Vromman, François; Perrinet, Stéphanie; Gehre, Lena; Subtil, Agathe (Frontiers in Cellular and Infection Microbiology, 2016)
Chlamydiae are Gram negative bacteria that develop exclusively inside eukaryotic host cells, within a membrane-bounded compartment. Members of the family Chlamydiaceae, such as Chlamydia trachomatis, are pathogenic species infecting vertebrates. They have a very reduced genome and exploit the capacities of their host for their own development, mainly through the secretion of proteins tailored to interfere with eukaryotic processes, called effector proteins. All Chlamydiaceae possess genes coding for four to five effectors that share a domain of unknown function (DUF582). Here we show that four of these effectors, which represent the conserved set in all Chlamydiaceae, accumulate in the infectious form of C. trachomatis, and are therefore likely involved in an early step of the developmental cycle. The fifth member of the family, CT621, is specific to C. trachomatis, and is secreted during the growth phase. Using a two-hybrid screen in yeast we identified an interaction between the host protein Hrs and the DUF582, which we confirmed by co-immunoprecipitations in co-transfected mammalian cells. Furthermore we provide biochemical evidence that a second domain of one of the DUF582 proteins, CT619, binds the host protein Tsg101. Hrs and Tsg101 are both implicated in a well conserved machinery of the eukaryotic cell called the ESCRT machinery, which is involved in several cellular processes requiring membrane fusion. Using RNA interference targeting proteins implicated at different stages of ESCRT-driven processes, or inhibition by expression of a dominant negative mutant of VPS4, we demonstrated that this machinery was dispensable for bacterial entry, multiplication and differentiation into infectious progeny, and for uptake of glycogen into the parasitophorous vacuole. In light of these observations we discuss how the DUF582 proteins might target the ESCRT machinery during infection.